2020
DOI: 10.1016/j.tra.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Does e-shopping for intangible services attenuate the effect of spatial attributes on travel distance and duration?

Abstract: E-shopping for intangible services (e.g., eating out services, hairdressing, and visits to movie theatres) refers to searching and paying for services online, but it requires e-shoppers to travel to use these services. In theory, e-shoppers' search space via the internet is less constrained by spatial attributes. As a result, spatial attributes may barely affect the distance and duration of trips resulting from e-shopping for intangible services. The present study used data from 714 valid face-to-face intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
(88 reference statements)
0
14
0
Order By: Relevance
“…One study (Bhat et al 2003 ) with longitudinal data also found a combination of the two effects (i.e., substitution and complementarity). A few studies found modification effects (Shi et al 2020a , 2020b ) when measuring changes in travel distances of online shoppers. Some studies also indicated the co-presence of multiple effects, such as complementarity and substitution (Etminani-Ghasrodashti and Hamidi 2020 ; Farag et al 2007 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One study (Bhat et al 2003 ) with longitudinal data also found a combination of the two effects (i.e., substitution and complementarity). A few studies found modification effects (Shi et al 2020a , 2020b ) when measuring changes in travel distances of online shoppers. Some studies also indicated the co-presence of multiple effects, such as complementarity and substitution (Etminani-Ghasrodashti and Hamidi 2020 ; Farag et al 2007 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared to detailed elements of the built environment, types of neighborhoods only provide limited information about the environment surrounding individuals' locations, possibly resulting in a weak link with online buying attitudes or behavior. In sum, future research needs to focus on more specific elements of the built environment surrounding a more appropriate place (e.g., workplace, primarily departure locations) instead of only residential places (Shi et al, 2019(Shi et al, , 2020a(Shi et al, , 2020bZhen et al, 2018).…”
Section: Built Environment and Online Purchasesmentioning
confidence: 99%
“…In theory, consumers' search spaces for destination information are considerably extended when they purchase online. As a result, consumers tend to travel farther to consume services ordered online, thus increasing the use of motorized modes (Shi et al, 2020a(Shi et al, , 2020b. In particular, Shi et…”
Section: Changes In Travel Caused By Online Purchasesmentioning
confidence: 99%
“…Here, the clients telling the comments when selling these items, the comments may be positive or negative. Therefore, the customers and the clients' opinions about the products are mentioned in the sentiment analysis (SA) 4–6 . The SA for product review is assessed for different online websites like https://flipkart.com, https://amazon.com, https://rediff.com 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the customers and the clients' opinions about the products are mentioned in the sentiment analysis (SA). [4][5][6] The SA for product review is assessed for different online websites like flipkart.com, amazon.com, rediff.com. 7,8 The SA facilitates both the seller and buyer, also it assists the seller to acquaint new products, then the buyer to detect the original products utilizing the user review on online websites.…”
mentioning
confidence: 99%